Pemberdayaan Masyarakat Berbasis Pemanfaatan Tanaman Obat untuk Kesehatan Keluarga di Desa Padang Pelawi, Kabupaten Seluma - Parwito, Parwito; Susilo, Edi; Rita, Wismalinda; Bustamam, Hendri; Widyaningsih, Sari; Syafitasari, Juanda; Putri, Poppy Siska; Yani, Sutri; Arifin, Ismail; Rismayani, Rismayani; Heltiani, Nofri (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
The aim of this community service activity is to empower the people of Padang Pelawi Village, Seluma Regency, in utilizing medicinal plants to improve family health. This activity was carried out through training in medicinal plant cultivation, herbal product processing, instant ginger production, and guidance on their use for everyday health. The implementation method used a participatory approach, involving the community directly in every stage of the activity. The first step was identifying local medicinal plants that could be used, followed by training on plant cultivation and how to process the harvest into beneficial products, such as instant ginger. Ongoing guidance was provided to ensure the sustainability of the activity and optimal management of the medicinal plants. The results of this activity show that the community has gained knowledge and skills in cultivating medicinal plants and processing them into useful products. Some families have already started growing medicinal plants in their yards and processing them into products that can be consumed or sold. Additionally, this activity has had an impact on increasing family income through the sale of medicinal plant products. This initiative successfully raised the community's awareness of the importance of utilizing medicinal plants as a natural and affordable health solution.